2011
DOI: 10.1080/00918369.2011.614906
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Factors Affecting Attitudes Toward Same-Sex Marriage: Do the Media Matter?

Abstract: Using a survey of more than 5,000 American consumers, this study examines connections between attitudes toward same-sex marriage and media consumption. A positive attitude is predicted by being liberal and less religious, supporting gender and racial equality, willing to try anything once, considering television the primary form of entertainment, watching political talk shows, and reading blogs. The theoretical and methodological contributions and real-world implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 39 publications
7
34
0
1
Order By: Relevance
“…Consistent with other work on positive minority portrayals and prejudice reduction, this research generally affirms that exposure to positive (explicit or implicit) messages about homosexuality is associated with more general positive affect toward sexual minorities, as well as greater support of civil rights for sexual minorities (Bonds-Raacke et al 2007;Calzo and Ward 2009;Lee and Hicks 2011;Schiappa, Gregg, and Hewes 2006). This effect is accomplished via both the content of the media, but also through the implicit negotiation of group identities and boundaries.…”
Section: Media Consumption and Public Opinionsupporting
confidence: 71%
“…Consistent with other work on positive minority portrayals and prejudice reduction, this research generally affirms that exposure to positive (explicit or implicit) messages about homosexuality is associated with more general positive affect toward sexual minorities, as well as greater support of civil rights for sexual minorities (Bonds-Raacke et al 2007;Calzo and Ward 2009;Lee and Hicks 2011;Schiappa, Gregg, and Hewes 2006). This effect is accomplished via both the content of the media, but also through the implicit negotiation of group identities and boundaries.…”
Section: Media Consumption and Public Opinionsupporting
confidence: 71%
“…In support of this, Lee and Hicks (2011) found that reading blogs on Internet and considering television the primary form of entertainment were positively associated with support towards same-sex marriage among adults from the United States. Furthermore, although Calzo and Ward (2009) did not find an overall effect of television viewing, they did find specific (positive or negative) effects depending on the gender or the demographic group.…”
Section: Discussionmentioning
confidence: 58%
“…For years, studies have been carried out on attitudes toward homosexuality, toward individuals with a homosexual sexual orientation, and toward their social rights (Herek, 2002;Lee & Hicks, 2011;Schwartz, 2010). The relationship between beliefs about the etiology of the homosexual sexual orientation and the rejection of gay men and lesbians has been studied by researchers from the point of view of attribution theory (Haider-Markel & Joslyn, 2008).…”
Section: Department Of Psychology University Of Valenciamentioning
confidence: 99%